2014
DOI: 10.2196/jmir.3062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Smartphone Medical Calculation Apps

Abstract: BackgroundMobile phones with operating systems and capable of running applications (smartphones) are increasingly being used in clinical settings. Medical calculating applications are popular mhealth apps for smartphones. These include, for example, apps that calculate the severity or likelihood of disease-based clinical scoring systems, such as determining the severity of liver disease, the likelihood of having a pulmonary embolism, and risk stratification in acute coronary syndrome. However, the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 10 publications
(11 reference statements)
2
53
0
4
Order By: Relevance
“…The evidence they report is inconclusive in terms of the impact on managing demand on professional time, patient experience and health outcomes. Diagnosis apps are found to be not always accurate and interactive symptom checkers may recommend professional care unnecessarily (Semigran et al, 2015, Bierbrier et al, 2014. However, online information appeared to help patients to manage their conditions and have more productive conversations with their GPs.…”
Section: Evidence On Impact From Related Interventionsmentioning
confidence: 99%
“…The evidence they report is inconclusive in terms of the impact on managing demand on professional time, patient experience and health outcomes. Diagnosis apps are found to be not always accurate and interactive symptom checkers may recommend professional care unnecessarily (Semigran et al, 2015, Bierbrier et al, 2014. However, online information appeared to help patients to manage their conditions and have more productive conversations with their GPs.…”
Section: Evidence On Impact From Related Interventionsmentioning
confidence: 99%
“…Apps are already an inextricable part of medical practice, and their use may open the door to adopting more sophisticated and complex methods of predicting weight without a negative effect on medical care [11,31]. An app which could automatically perform the calculations required for a weight estimate as well as drug doses (based on the most appropriate weight-descriptor for drug type and habitus type) could reduce medication errors.…”
Section: Weight Estimation During Emergenciesmentioning
confidence: 99%
“…These systems can eliminate the need for calculations for weight-estimation systems in addition to providing comprehensive drug-dosing information [11]. The use of such devices could also allow for more complex weight estimation methodologies to be used without generating a debilitating cognitive burden.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Other authors reasoned that with trustworthy and validated apps, health care professionals can be more confident about employing smartphones in a clinical setting. [19] Students' experience We found that the surveyed students would like to use the app in areas where students typically use mobile devices already, in areas that are obviously related to medical education and in those that can be expected to be related to clinical work (e.g. during the final year or when starting postgraduate education).…”
Section: Contact To Universitymentioning
confidence: 99%